SUBMITTING OF DECISIONS OF THE INVERSE LINEAR PROBLEM OF GRAVITY APPLYING AUTOMATED PROGRAM MICROSYSTEMS FOR STUDYING OF TECTONIC ZONES ON THE BUILT UP TERRITORIES OF ECOLOGICALLY DANGEROUS OBJECTS - MINENKO, P.; MINENKO, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
In the software it is included a number of special author's methods of the decision of return problems gravity which complex use is a necessary condition for effective studying tectonic zones in files of rocks of the crystal base.